The Essence of Patience in Imam Al-Ghazali’s Perspective: An Ethical and Spiritual Analysis in Ihya’ ‘Ulum al-Din - Subhi, Muhibbul; Nasir, M.; Ridha, Ismu; Samwil, Samwil; Nova, Mirza Adia; Husna, Fathayatul (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This study examines the essence of patience (sabr) from the perspective of Imam Al-Ghazali through an ethical-spiritual analysis in Ihya’ Ulum al-Din. The background of this research is based on the increasing moral crisis, psychological pressures, and weakening self-control in modern life, making the concept of patience highly relevant to be reexamined as a foundation for the development of human morality and spirituality. This study aims to analyze the nature of patience according to Al-Ghazali, its various forms, and its relevance to modern life. The research employs a qualitative approach using the library research method. Primary data are derived from Ihya’ Ulum al-Din, while secondary data are obtained from various books, journals, and relevant scholarly works. Data analysis is conducted through content analysis and descriptive-qualitative methods. The findings reveal that patience, according to Al-Ghazali, is not merely a passive attitude in accepting trials, but rather an active ethical-spiritual force in controlling desires, maintaining obedience to God, and facing hardships with steadfast faith. Al-Ghazali classifies patience into several forms: patience in obedience, patience in avoiding sins, patience in facing calamities, and patience in dealing with worldly pleasures. The concept of patience is also closely related to tazkiyat al-nafs (purification of the soul), moral formation, and the spiritual journey toward closeness to Allah. In the modern context, Al-Ghazali’s concept of patience remains relevant as an ethical and spiritual solution to moral crises, psychological pressures, instant culture, and social conflicts in contemporary society. Therefore, patience in Al-Ghazali’s perspective serves as an essential foundation for character building, mental resilience, and spiritual balance in human life